Pengembangan Media Pembelajaran Game Education pada Mata Pelajaran Bahasa Inggris Materi My Body - Ma’rufah, Rosidiana; Ghoni, Abdul (Program Studi PGMI STAI Auliaurrasyidin Tembilahan, 2021)
The media game of education in this study referred to the overview of the basic body along with pictures to attract students' attention. The type of research used in this study was Research and Development (R&D). R&D is a research strategy or method that is powerful enough to improve practice. The data were collected through questionnaires, interviews, and documentation. The object was to measure the success of the learning process as evidenced by the student's scores. The variable used as a measurement was the feasibility of the product. The results showed that the need for game education in learning was an important medium to make the teachers easier delivering the learning material, attracting students, especially for grade 1 students at Madrasah Ibtidaiyah, students were also easier to master the topic about my body. The development of learning media for game education can be used by students not only when learning at school. The effectiveness test using the SPSS program also showed the value of Sig. (2-tiled) p = 0.000 <0.05, which means that game media education was effective to improve English learning outcomes about my body.